A cross-sectional analysis of gender and psychological well-being among older Taiwanese adults - Fergus, Deleon N.; Chen, Yi-Hua; Chuang, Ying-Chih; Ma, Ai-hsuan Sandra; Chuang, Kun-Yang (Frontiers in Psychology, 2024)
Psychological well-being (PWB) facilitates good health. Few studies have taken into consideration gender and how it can affect PWB within a sociocultural context. This study aims to determine if relationships between social, health, behavioral, and socioeconomic factors on PWB among older Taiwanese adults are affected by gender.Data were obtained from the 2016 Taiwan Mental Health Survey. A representative sample, of 2,286 individuals, was created using multistage proportional probability. Participants were interviewed at their homes using a structured questionnaire. Inclusion criteria were Taiwanese citizenship, age ≥55 years, and the ability to provide informed consent. Participants 65 years and above were selected for the study sample n=1,533. An 18-item version of Ryff's PWB scale was used to determine PWB. The median value was used to categorize low and high PWB. Logistic regression analyses were used to examine predictors of PWB stratified by gender.Chronic disease, unemployment, and financial dependence negatively impacted men's PWB. Satisfaction with living environment and family relationships positively impacted women's PWB. Unique characteristics of older men, women, and culture account for this.Gender-specific interventions aimed at promoting PWB in older adults are needed. Recommendations include educational programs, social support workshops, and community engagement initiatives.